Os meandros do processo de alfabetização e a incidência de exclusão escolar: um estudo em escolas municipais de São Leopoldo - Urmersbach, Regina (Universidade do Vale do Rio do Sinos, 2007)
The objective of this study is to examine the learning processes on the beginning years of the elementary school, seeking to identify and describe potencial situations of the exclusion process on schools, restricted to the classroom environment, focusing the process of the reading and writing. In order to achieve the proposed objective it has been developed a research. I qualitative with 22 teachers and 44 students from 11 elementary school from São Leopoldo –Rio Grande do Sul Brazil. In order to collect the data the following research instruments were used: a questionnaire, a applied to the teachers, an interview, carried through with students of the same classes where the questionnaires were applied and observation of these classrooms, besides a sample of the teachers class logbooks. The school experience, specially the one referred to the first year of the elementary school in which the alphabetization process is developed, is an important stage for the formaction of the reader and the writer. The standard
Keywords: alfabetização; ensino fundamental; sala de aula; exclusão escolar; alfabetizacion; classroom; elementary schools; schools exclusion; Ciências Humanas